Perlindungan Hukum terhadap Perempuan dan Anak Korban Kekerasan dalam Rumah Tangga (Studi Kasus pada Lembaga Konsultasi Kesejahteraan Keluarga Kota Cimahi) - Nuradhawati, Rira; Nurcahyono, Arinto (Wajah Hukum, 2025)
Legal protection for victims of domestic violence is very important to do considering the physical and psychological suffering experienced by victims as a result of the actions of the perpetrator. According to Article 1 paragraph (1) of Law Number 23 Year 2004 on the Elimination of Domestic Violence, what is meant by domestic violence is ‘any act against a person, especially women, which results in physical, sexual, psychological, and or domestic neglect, including threats to commit acts, coercion, or unlawful deprivation of independence within the scope of the household’. Sociologically, domestic violence is often influenced by patriarchal structures that are still dominant in many societies. In addition, social and cultural norms that consider domestic violence as a private matter are also an obstacle in handling this case. This research uses empirical juridical method, which is a research method that seeks to see the law in real terms or examines how the law works in society.  LK3 as an Integrated Social Service Unit provides an alternative for the community in overcoming family psychosocial problems, restoring family psychosocial conditions, and strengthening family resilience. Based on the results of the research that legal protection is one of the functions of LK3 Cimahi City towards women victims of domestic violence, it is considered to be quite optimal. This can be seen from how protection is provided through a series of roles, be it active, participatory or passive roles.